Becoming a Caregiver: The Role of the Environment in the Process of Children Becoming Responsible for Others - Carolina Remorini (Behavioral Sciences)
This article aims to illustrate the pivotal role that the environment plays in early child development (ECD), drawing upon data derived from the ethnographic research on children’s daily routines. Participant observation and in-depth interviews were conducted over the course of several fieldwork periods (2013–2018). The concept of “mutual raising” is employed to examine the daily interactions between middle-aged children and their domestic animals. To gain an insight into how children develop sophisticated and ecologically relevant skills to become autonomous and responsible for the care of others within the context of environmental interdependence, we present and analyze a cultural practice that is salient to the identity and way of life in rural communities of the Andean region in South America: becoming a shepherd. Considering the aforementioned findings, it can be posited that being able to care for others represents a significant developmental milestone. This discussion highlights the limitations of the dominant theoretical and disciplinary lens through which ECD is currently studied, those so-called W.E.I.R.D societies. Consequently, it is imperative to advocate for an integrative and transdisciplinary framework for ECD studies that incorporates anthropological evidence and the cultural experiences of children and families who have been historically marginalized by dominant ECD models.